(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
A variety of applications involving animals and humans make use of polyethylene glycol (PEG). Because the toxicity of various PEGs is becoming increasingly apparent and has been documented several times, their removal from polluted regions is urgently required. Several studies have shown and advocated that PEG biodegradation by microorganisms may be a viable approach for remediating PEG-contaminated landfills. As a result of Malaysia’s huge number of landfills, which is likely to expand in the future, it is believed that PEG contamination would rise as well, and the use of PEG-degrading microorganisms may benefit the country. This review aimed to summarize and update information on PEG-degrading microorganisms so that the information compiled can benefit local researchers in isolating more efficient PEG-degraders. The absorption of PEGS into energy under aerobic and anaerobic systems includes a variety of enzyme chains, which will present a challenge that needs to be addressed in future isolation of PEG-degraders and the elucidation of the degradation mechanisms.